Endometrial polyps in female allograft recipients with abnormal bleedings - Dariusz Rajski; Katarzyna Bobrowska; Bronisława Pietrzak; Mirosław Wielgoś; Paweł Kamiński (Menopause Review, 2014)
Introduction : Endometrial polyps are a common focal endometrial pathology, with abnormal uterine bleeding (AUB) as a predominant symptom. Although the great majority of cases are benign, premalignancy or malignancy may develop within the polyp. The need for chronic immunosuppressive therapy in solid organ transplanted patients is associated with a significantly increased risk of malignant lesions. Aim of the study was to evaluate the risk of endometrial polyps in solid organ transplanted women with abnormal uterine bleeding. Material and methods : The retrospective analysis of 125 cases of AUB in allograft recipients and 200 consecutive cases of AUB in patients from the general population was performed. Pathological findings from dilatation and curettage were analyzed and compared between the groups. Results : Endometrial polyps were the only pathological findings in 12% and 21.5% of cases from the study and the control groups, respectively. In each of the groups, one case of endometrial cancer coexisted with an endometrial polyp. If cases of endometrial polyps coexisting with endometrial hyperplasia were taken into account, the rate of endometrial polyps was similar to that observed in the general population (20% vs. 21.5%, respectively). Conclusions : Chronic immunosuppression, associated with an increased risk of malignancy, does not increase the risk of endometrial polyps among female graft recipients.